In Silico Prediction And In Vitro Evaluation Of Caffeic Acid And Its Derivatives As Potential Efflux Pump Inhibitor(S) In Pseudomonas Aeruginosa - Zakaria, Noor Zawani (2019)
Pseudomonas aeruginosa is a bacterial pathogen that is intrinsically resistant towards various antibiotics. The main factors that contribute to this intrinsic resistance are due to the lower outer membrane permeability and expression of multiple efflux pumps. One of the promising strategies to circumvent the problem of bacterial resistance is the use of efflux pump inhibitor (EPI). In this study, the efflux pump inhibitory potential of caffeic acid and its derivatives were predicted using in silico molecular docking, and accessed using in vitro ethidium bromide (EtBr) accumulation assay. Two proteins (MexB and MexY) that play important roles in the effluxing of antibiotics in P. aeruginosa were used as the target proteins. Based on the protein-ligand interaction studies, caffeic acid phenethyl ester (CAPE) and caffeic acid phenethyl amide (CAPA) that scored the lowest free energy of binding in both proteins were identified as potential EPI candidates. The potential of caffeic acid, CAPE and CAPA to act as EPIs in P. aeruginosa was evaluated using ethidium bromide (EtBr) accumulation assay. Among the three compounds tested, CAPE was found to significantly increase the intracellular accumulation of EtBr in P. aeruginosa. An increase of 21.4% in fluorescence over 5- min time frame was observed in P. aeruginosa. This suggests that CAPE was able to disrupt or compromise the efflux pumps, thus leading to the accumulation of EtBr in these bacterial cells.